Development of a New Sesame Product using QFD and DOE methods: A Case Study of Sesame Product in Yazd - Habib Zare Ahmadabadi; Fatemeh Zamzam; Farahnaz Rahmani Meybodi; Dalia Streimikiene; Abbas Mardani (Montenegrin Journal of Economics, 2018)
The aim of the study is to identify customer’s needs for new sesame products, converting requirements into product and process qualitative characteristics, and improving the new product quality. Based on morphological approach and point of views of the manufacturers of sesame products and customers(384 persons), new ideas were extracted and between them a chocolate sesame product was selected. By coducting a survey of consumer expectations(382 sample) taste of new product was examined and translated into technical specifications. The paper considers the implementation of the Quality Function Deployment (QFD) and DOE in BAH(Booz, Allen and Hamilton) framework for the development of new food products. It also aims to meet the challenge of satisfying customer’s inconstant demands and, in turn, to make the business thrive. The results show that main quality features for final product are in good taste, no bitter-taste and be Fresh. Satisfying these requirements are relative to parameters such as sesame variety, chocolate melting point, control of cooking time and oven temperature